2009
DOI: 10.1109/jlt.2009.2020303
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of InP APDs for High-Speed Lightwave Systems

Abstract: Abstract-Calculations based on a rigorous analytical model are carried out to optimize the width of the indium phosphide avalanche region in high-speed direct-detection avalanche photodiode-based optical receivers. The model includes the effects of intersymbol interference (ISI), tunneling current, avalanche noise, and its correlation with the stochastic avalanche duration, as well as dead space. A minimum receiver sensitivity of 28 dBm is predicted at an optimal width of 0.18 m and an optimal gain of approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Since band to band tunneling is inversely proportional to the exponential of the band gap, using a wider-gap semiconductor as the multiplication region in an APD should lead to a lower tunneling current. 4 The temperature dependence of avalanche multiplication characteristics and breakdown voltage in several widegap semiconductors have been previously reported. Ma et al 5 reported that Al x Ga 1-x As with an Al composition of 60% has the smallest C bd in the Al x Ga 1-x As material system for a given avalanche region thickness, w. Groves et al have reported a C bd of 3.18 mV/K for a w ¼ 0.09 lm Al 0.6 Ga 0.4 As p þ -i-n þ diode.…”
Section: Introductionmentioning
confidence: 96%
“…Since band to band tunneling is inversely proportional to the exponential of the band gap, using a wider-gap semiconductor as the multiplication region in an APD should lead to a lower tunneling current. 4 The temperature dependence of avalanche multiplication characteristics and breakdown voltage in several widegap semiconductors have been previously reported. Ma et al 5 reported that Al x Ga 1-x As with an Al composition of 60% has the smallest C bd in the Al x Ga 1-x As material system for a given avalanche region thickness, w. Groves et al have reported a C bd of 3.18 mV/K for a w ¼ 0.09 lm Al 0.6 Ga 0.4 As p þ -i-n þ diode.…”
Section: Introductionmentioning
confidence: 96%
“…The model in this paper is based on the bit-error-rate (BER) model developed in [1] and [2], although there are some significant differences and modifications which need to be discussed. The unique impulse response of an e-APD means that many of the equations previously developed cannot be used, and a revision of the model must be carried out.…”
Section: A Review Of the Model Reported In [2]mentioning
confidence: 99%
“…We emphasize, however, that the limitation of the model in [2] arises only when an analytical formula for the receiver sensitivity is sought; the model in [2] remains valid for the numerical calculation of the sensitivity for electron APDs, though this would require significantly more computing resources to match the accuracy provided by a more analytical model. Although the analytical expressions for the mean and variance of the APDs stochastic impulse response function from [2] are no longer valid, the defining integrals for the mean and the variance are still valid and can still be used.…”
Section: A Review Of the Model Reported In [2]mentioning
confidence: 99%
See 2 more Smart Citations